Detection of Cerebrospinal Fluid Neurofilament Light Chain as a Marker for Alpha-Synucleinopathies - Canaslan, Sezgi; Schmitz, Matthias; Villar-Piqué, Anna; Maass, Fabian; Gmitterová, Karin; Varges, Daniela; Lingor, Paul; Llorens, Franc; Hermann, Peter; Zerr, Inga (Frontiers in Aging Neuroscience, 2021)
Alpha synucleinopathies, such as Parkinson’s disease (PD), dementia with Lewy-bodies (DLB), or multiple system atrophy (MSA), are a class of neurodegenerative diseases. A diagnosis may be challenging because clinical symptoms partially overlapped and there is currently no reliable diagnostic test available. Therefore, our aim was to identify a suitable marker protein in cerebrospinal fluid (CSF) to distinguish either between different types of alpha synucleinopathies or between alpha synucleinopathies and controls. In the present study the regulation of different marker protein candidates, such as alpha synuclein (a-syn), neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), and total tau (tau) in different types of alpha synucleinopathies had been analysed by using an ultrasensitive test system, called single molecule measurement assay (SIMOA). Interestingly, we observed CSF-NfL significantly elevated in DLB and MSA compared to PD-patients or control donors. To differentiate between groups, receiver operating characteristic (ROC) curve analysis resulted in a very good diagnostic accuracy as indicated by the area under the-curve (AUC) values of 0.86 – 0.92 for CSF-NfL Moreover, we observed GFAP and tau slightly increased either in DLB or in MSA, while a-syn-levels remained unregulated. Our study suggests NfL as a promising marker to discriminate different types of alpha synucleinopathies or between DLB/MSA and controls.